The Power of Digital Silence: A Conceptual Analysis of the ‘Read Receipt’ as a Micro-Power Practice - Akyüz, Eyyüp (Information & Media, 2026)
This conceptual study explores the sociological and psychological dynamics of digital silence following ‘read receipts’ in instant messaging. Methodologically grounded in critical conceptual analysis, the study synthesizes empirical findings from cyber-psychology with classical and contemporary sociological frameworks (focusing on power, temporality, and emotional capitalism). The analysis suggests that, in a digital age characterized by speed and forced transparency, reading a message and leaving it unanswered can function as an asymmetrical micro-power domain. On the receiver’s end, this silence may be strategically instrumentalized for boundary maintenance, tactical agency, and consumption-oriented relationship management. Conversely, on the sender’s end, prolonged inaction has the potential to trigger feelings of cyberostracism, which can lead to anxiety and an internalized sense of subjection. Ultimately, the article proposes that digital inaction is not merely a void interruption, but, rather, a structurally laden message through which interacting parties attempt to navigate power dynamics by concealing their true intentions.